Organic food consumption in Kenitra, Morocco: attitudes, motivations, and barriers - Lafram, Amina; Belfakira, Chaimaa; Hindi, Zakia; Bikri, Samir; Benayad, Asmaa; El Bilali, Hamid; Bügel, Susanne Gjedsted; Średnicka-Tober, Dominika; Pugliese, Patrizia; Strassner, Carola; Rossi, Laura; Stefa-novic, Lilliana; et al. (Frontiers in Sustainable Food Systems, 2024)
This study aims to evaluate organic food consumption as well as to understand the underlying factors influencing the consumption patterns, including consumers' preferences and motivations as well as the challenges they face in Kenitra (Morocco). Data was collected through an anonymous household survey involving 442 respondents, targeting the population of Kenitra. The findings reveal that in 60% of the Kenitra households organic foods comprise 1-25% of all the foods consumed, highlighting a growing interest in these products. However, several barriers were identified, including insufficient availability and accessibility of organic products, as well as limited product variety at local shopping places, and the perceived high prices of organic foods, which continue to hinder organic food consumption. Moreover, consumers expressed a need for better access to organic products and emphasized the importance of reasonable pricing, considering it as a significant factor in their decisionmaking process. Understanding the dynamics of organic food consumption in Kenitra and the eating attitudes and behaviours of its residents will provide valuable insights that can be employed to reshape future local policies, strategies, and market developments, in response to the changing demands and preferences of the population while promoting the adoption of organic food in the region and the whole country.